ANALISA UJI IMPAK BAJA CARBON STEEL 1045 DENGAN MENGGUNAKAN METODE CHARPY - muhammad wahyu (Jurnal Simetri Rekayasa, 2020)
Carbon steel 1045 is a material that is widely used for machine components. Due to its malleability and good machinability, and good heat resistance and ductility. The design and impact testing of charpy is a material analysis to determine the toughness or brittleness of the material against sudden loads. By heating the 1045 carbon steel material, using the hardening method using water media to determine the brittleness of carbon steel after being heated. The results obtained after testing were that the impact energy value obtained from specimen1 was greater with a value of 125.739 joules, while for specimen 2 (117.5603 joules) and specimen 3 (103.833 joules). The value of the impact value obtained by specimen 1 was greater with a value of 0.235 j/for specimen 1 while 0.213 j/for specimen 2 and 0.188 j/ for specimen 3. The lower the impact value obtained, the more resilient the fracture occurs in the specimen.